The Use of Calculus in Optimizing the Performance of Computation-Based Information Systems - Anggie Rahmadani; Aqtika Soleha (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2026)
This research aims to explain the role of calculus in optimizing the performance of computational-based information systems. In this context, calculus is used to solve problems related to algorithm efficiency, data modeling, and system performance analysis. The research method used is a literature review that includes studies on the application of calculus in various aspects of information technology and computation. The results indicate that the use of calculus, particularly in differential and integral analysis, can improve data processing speed and computational accuracy in information systems. In conclusion, calculus plays an important role in the development of modern information systems, particularly in improving efficiency and system performance. The rapid development of computation-based information systems requires optimal performance in terms of processing speed, resource efficiency, and accuracy. One mathematical approach that plays a crucial role in achieving such optimization is calculus. This study aims to examine the use of calculus concepts, particularly derivatives and integrals, in improving the performance of computation-based information systems.